Ten fish mitogenomes of the tribe Gobionini (Cypriniformes: Cyprinidae: Gobioninae). Issue 2 (3rd July 2018) - Li, Yuhuo; Cao, Kai; Fu, Cuizhang
Abstract: Freshwater fishes of the subfamily Gobioninae (Cypriniformes: Cyprinidae) are composed of three major clades, the tribes Gobionini and Sarcocheilichthyini, and a Hemibarbus – Squalidus group. In this study, we determined ten complete fish mitogenomes from eight of all twelve genera in the tribe Gobionini. The ten mitogenomes displayed similar patterns in gene arrangements, codon use and gene overlaps with the length of 16, 605–16, 617 bp and base compositions slightly A + T bias of 56.1–58.0%. Our phylogeny of the tribe Gobionini revealed that the genera Gobio, Xenophysogobio, Gobiobotia, Saurogobio and Pseudogobio were monophyletic, and other genera Abbottina, Biwia, Microphysogobio and Platysmacheilus were paraphyletic or polyphyletic. The findings indicate that the genera classifications of Gobionini are needed to be further confirmed.